2017
DOI: 10.1371/journal.pone.0189600
|View full text |Cite
|
Sign up to set email alerts
|

Nucleases as a barrier to gene silencing in the cotton boll weevil, Anthonomus grandis

Abstract: RNA interference (RNAi) approaches have been applied as a biotechnological tool for controlling plant insect pests via selective gene down regulation. However, the inefficiency of RNAi mechanism in insects is associated with several barriers, including dsRNA delivery and uptake by the cell, dsRNA interaction with the cellular membrane receptor and dsRNA exposure to insect gut nucleases during feeding. The cotton boll weevil (Anthonomus grandis) is a coleopteran in which RNAi-mediated gene silencing does not fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 108 publications
(137 reference statements)
2
31
0
Order By: Relevance
“…The gut nucleases in hemipteran insects are reported as major bottleneck in efficient RNAi, as these enzymes hamper the concentration of dsRNA reaching the cell (Huvenne and Smagghe, 2010;Joga et al, 2016). Besides hemipteran, the degradation of dsRNA by dsRNases have also been reported from other insect orders (Almeida Garcia et al, 2017;Singh et al, 2017;Prentice et al, 2019;Song et al, 2019). Our studies successfully demonstrated the degradation of dsRNA in hemolymph and gut juices of whitefly.…”
Section: Results and Discussion Dsrna Degradation Studies And Enhancisupporting
confidence: 62%
“…The gut nucleases in hemipteran insects are reported as major bottleneck in efficient RNAi, as these enzymes hamper the concentration of dsRNA reaching the cell (Huvenne and Smagghe, 2010;Joga et al, 2016). Besides hemipteran, the degradation of dsRNA by dsRNases have also been reported from other insect orders (Almeida Garcia et al, 2017;Singh et al, 2017;Prentice et al, 2019;Song et al, 2019). Our studies successfully demonstrated the degradation of dsRNA in hemolymph and gut juices of whitefly.…”
Section: Results and Discussion Dsrna Degradation Studies And Enhancisupporting
confidence: 62%
“…These studies demonstrate the importance of evaluating the RNAi sensitivity by microinjection as well as by feeding in the target insect species since it is not possible to predict the RNAi effectiveness based on the RNAi response found in other insects, even in closely related species. The activity of dsRNA degrading enzymes (dsRNase) in the insect gut lumen can impair the RNAi response and has been considered one of the main factors that leads to differences in the level of RNAi sensitivity through dsRNA ingestion among insect species …”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that rapid dsRNA degradation by some nucleases can cause differences in dsRNA sensitivity among organisms (Wang et al ., ; Singh et al ., ). The two types of nuclease that are likely to be involved in dsRNA degradation are exonucleases and endonucleases (Kupsco et al ., ; Gabel and Ruvkun, ; Ramachandran and Chen, ; Garbutt et al ., ; Wynant et al ., ; Garcia et al ., ; Song et al ., ; Cao et al ., ; Guan et al ., ). Exonucleases work at the termini of the dsRNAs; so, short molecules that are capable of binding exonucleases for long enough to activate them have more ends and are more easily degraded by the exonucleases than are long molecules of similar weight.…”
Section: Discussionmentioning
confidence: 98%